Draft Annual Plan 1988-89 Volume II Union Territory of Chandigarh - Planning Commission (Planning Commission, 1988)
Head of Development Outlay and Expenditure Development of Scheme/Project Outlay and Expenditure Physical Targets and Achievements Minimum Needs Programme-Outlay and Expenditure Minimum Needs Programme-Physical Targets and Achievements Employment Content of Plan Scheme-Outlay and Expenditure and Targets and Expenditure.
Planning and Evaluation Organisation, Finance Department, Chandigarh Administration